Anisotropy of Crumbs and aPKC Drives Myosin Cable Assembly during Tube Formation. - Roper, K. (Developmental Cell, 2012)
The formation of tubular structures from epithelial sheets is a key process of organ formation in all animals, but the cytoskeletal rearrangements that cause the cell shape changes that drive tubulogenesis are not well understood. Using live imaging and super-resolution microscopy to analyze the tubulogenesis of the Drosophila salivary glands, I find that an anisotropic plasma membrane distribution of the protein Crumbs, mediated by its large extracellular domain, determines the subcellular localization of a supracellular actomyosin cable in the cells at the placode border, with myosin II accumulating at edges where Crumbs is lowest. Laser ablation shows that the cable is under increased tension, implying an active involvement in the invagination process. Crumbs anisotropy leads to anisotropic distribution of aPKC, which in turn can negatively regulate Rok, thus preventing the formation of a cable where Crumbs and aPKC are localized.